Nurse contributions to the self-care of chronic renal patients: Interfaces for care (Research, Society and Development, 2022)
Chronic Kidney Disease (CKD) has become a serious public health problem in Brazil and in the world, it occurs when the kidneys lose the ability to fulfill some of the main functions assigned to the body, such as: maintaining the balance of electrolytes and promote blood filtration, has two forms of impairment, which are acute and chronic. In view of this situation, the nursing professional presents himself as a fundamental piece to guide self-care in the process of coping with the renal patient's treatment. In view of the above, this study has the general objective: to understand the self-care practices of the chronic renal patient and as specific objectives: To identify, through the literature, the level of knowledge of the CKD patient for self-care, to describe the nurses' guidelines for the patient's self-care with CKD. The methodology was carried out through a literature review of a qualitative approach of an exploratory nature through bibliographic research, the VHL and Google scholar were chosen as a database, where 20 articles were selected, which gave rise to three categories: Knowledge of the renal patient chronic about his hemodialysis treatment; Information passed by the nurse to the patient on hemodialysis with regard to self-care. It is concluded that the nurse has a fundamental role in welcoming this patient, solving their doubts, fears, explaining about their pathology, encouraging them to perform self-care, how to take care of their catheter to avoid the risk of infection, and fulfill their daily needs.